2019
DOI: 10.1097/ccm.0000000000003799
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Distribution Width: A Novel Indicator of Sepsis-2 and Sepsis-3 in High-Risk Emergency Department Patients*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 30 publications
6
59
3
Order By: Relevance
“…(2017) first reported that increased MDW values correlated with sepsis in a large sample of patients presenting at an Emergency Department in Ohio [9]; they showed that a value of greater than 20.0 of MDW was effective for sepsis detection based on either Sepsis-2 criteria or Sepsis-3 criteria in a multicenter study enrolling patients from 3 emergency departments [29]. As a consequence, a 2-point difference between their better threshold and ours seems to exist.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…(2017) first reported that increased MDW values correlated with sepsis in a large sample of patients presenting at an Emergency Department in Ohio [9]; they showed that a value of greater than 20.0 of MDW was effective for sepsis detection based on either Sepsis-2 criteria or Sepsis-3 criteria in a multicenter study enrolling patients from 3 emergency departments [29]. As a consequence, a 2-point difference between their better threshold and ours seems to exist.…”
Section: Discussionmentioning
confidence: 85%
“…Haydar et al (2017) reported the qSOFA score was efficacious for the identification of patients with sepsis at increased risk of mortality, while performing poorly as a screening tool for early identification of sepsis in the emergency department [33]. In low intensity settings, the use of MDW might therefore become a low-cost alternative to PCT for early detection of ongoing sepsis [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine-producing monocyte population is an element of the innate immunity undergoing transformation not only in terms of functionality but also in their morphology [14] . These changes in response to infection are at the basis of the modification of the MDW parameter observed in different types of infection [3] , [4] , [5] .…”
Section: Discussionmentioning
confidence: 97%
“…Monocyte Distribution Width (MDW) is an in vitro diagnostic parameter automatically reported in the Complete Blood Count with differential (CBC-Diff) and routinely requested at the Emergency Department. It has been demonstrated that an elevated MDW value is effective for early detection of sepsis in adult patients presenting at the Emergency Department (ED) [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they proposed that this value may be useful to identify high-risk patients with an idiopathic pulmonary fibrosis [11]. It is supposed that the monocyte level may be a useful biomarker of other illnesses, such as coronary heart disease [12], sepsis-2 and sepsis-3 [13], amyotrophic lateral sclerosis [14], and many more. Here, the phase of tissue repair should be highly controlled and resolves quickly to restore normal tissue architecture [10].…”
Section: Subsets Of Monocytes and Their Main Functionsmentioning
confidence: 99%